Five years investigation of female and male genotypes in périgord black truffle (Tuber melanosporum Vittad.) revealed contrasted reproduction strategies. (5th May 2017) - De la Varga, Herminia; Le Tacon, François; Lagoguet, Mélanie; Todesco, Flora; Varga, Torda; Miquel, Igor; Barry‐Etienne, Dominique; Robin, Christophe; Halkett, Fabien; Martin, Francis; Murat, Claude
Summary: The Périgord black truffle ( Tuber melanosporum Vittad.) is a heterothallic ascomycete that establishes ectomycorrhizal symbiosis with trees and shrubs. Small‐scale genetic structures of female genotypes in truffle orchards are known, but it has not yet been studied in male genotypes. In this study, our aim was to characterize the small‐scale genetic structure of both male and female genotypes over five years in an orchard to better understand the T. melanosporum sexual reproduction strategy, male genotype dynamics, and origins. Two‐hundred forty‐one ascocarps, 475 ectomycorrhizas, and 20 soil cores were harvested and genotyped using microsatellites and mating type genes. Isolation by distance analysis revealed pronounced small‐scale genetic structures for both female and male genotypes. The genotypic diversity was higher for male than female genotypes with numerous small size genotypes suggesting an important turnover due to ascospore recruitment. Larger and perennial female and male genotypes were also detected. Only three genotypes (1.5%) were found as both female and male genotypes (hermaphrodites) while most were detected only as female or male genotype (dioecy). Our results suggest that germinating ascospores act as male genotypes, but we also proposed that soil mycelium could be a reservoir of male genotypes.